Development of a pain education resource for people with spinal cord injury - Widerström-Noga, Eva; Anderson, Kimberly D.; Robayo, Linda E.; Perez, Salome; Martinez-Arizala, Alberto; Calle-Coule, Lindsey; Cherup, Nicholas P.; Fernandez, Gabriel E. (Frontiers in Public Health, 2023)
Many people with spinal cord injury (SCI) develop chronic pain, including neuropathic pain. Unfortunately, current treatments for this condition are often inadequate because SCI-associated neuropathic pain is complex and depends on various underlying mechanisms and contributing factors. Multimodal treatment strategies including but not limited to pharmacological treatments, physical rehabilitation, cognitive training, and pain education may be best suited to manage pain in this population. In this study, we developed an educational resource named the SeePain based on published pain literature, and direct stakeholder input, including people living with SCI and chronic pain, their significant others, and healthcare providers with expertise in SCI. The SeePain was then 1) systematically evaluated by stakeholders regarding its content, comprehensibility, and format using qualitative interviews and thematic analysis, and 2) modified based on their perspectives. The final resource is a comprehensive guide for people with SCI and their significant others or family members that is intended to increase health literacy and facilitate communication between SCI consumers and their healthcare providers. Future work will quantitatively validate the SeePain in a large SCI sample.